2010
DOI: 10.1364/oe.18.002495
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous compression and amplification of a laser pulse in a glass plate

Abstract: We demonstrated a novel method of simultaneous compression and amplification of a weak laser pulse in a glass plate using cross-phase modulation in conjunction with four-wave optical parametric amplification that was pumped by an intense femtosecond pulse. A proof-of-principle experiment succeeded in smooth broadening of the weak pulse spectrum by a factor of about three and simultaneously amplifying the pulse energy by more than three times. By using chirped mirrors to compensate the dispersion, the weak puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…4(f). We have also observed that an increase of the pump energy leads to a spectral broadening of the near-IR pulse, as a result of the cross-phase modulation (XPM) between the pump and seed pulses inside the fused silica sample, as noted in similar experiments [18,24]. We have found that the XPM-broadened pulses are still fully compressible, and indeed, the measured pulse durations, after optimization of the pulse compressor, have been shorter by ∼10-20%.…”
Section: Generation Of Sub-30 Fs Pulses By Noncollinear Optical Paramsupporting
confidence: 62%
“…4(f). We have also observed that an increase of the pump energy leads to a spectral broadening of the near-IR pulse, as a result of the cross-phase modulation (XPM) between the pump and seed pulses inside the fused silica sample, as noted in similar experiments [18,24]. We have found that the XPM-broadened pulses are still fully compressible, and indeed, the measured pulse durations, after optimization of the pulse compressor, have been shorter by ∼10-20%.…”
Section: Generation Of Sub-30 Fs Pulses By Noncollinear Optical Paramsupporting
confidence: 62%
“…A concave mirror with a focal length of 600 cm was used to focus Beam 1 into the nonlinear medium (G1). Beam 2 was focused into the nonlinear medium by a lens with a focal length of 1 m. The fourth beam (Beam 4) was used to characterize the generated multicolored pulses with the cross-correlation frequency-resolved optical gating (XFROG) technique [74] in a 10 µm-thick BBO crystal. Type-1 experimental setup.…”
Section: Experimental Setupsmentioning
confidence: 99%
“…G1: nonlinear medium for multicolored sidebands generation. G2: nonlinear medium for pulse measurement with an X-FROG system [74]. Figure 4 shows the schematic of Type-2 setup, which was used for the generation of low-threshold multicolored sidebands and 2-D multicolored arrays in a diamond plate.…”
Section: Experimental Setupsmentioning
confidence: 99%
“…Argon gas filled in the hollow-core fiber has broadened spectral width to generate a few-optical-cycle broadband ultraviolet (UV) pulse [27]. The broadened spectrum coming out from the hollow-core fiber was extending from 360 to 440 nm.…”
Section: Ultraviolet Few-optical-cycle Pulsesmentioning
confidence: 99%
“…In this work, the Claisen rearrangement was studied directly by observing the reaction process through time-resolved vibration spectroscopy using a pulsed laser with few optical cycles [26,27]. Direct observation of the Claisen rearrangement has not been performed by any other methods to date.…”
Section: Introductionmentioning
confidence: 99%